Chemical shipments through the straits of Malacca: An analysis from a Malaysian legal perspective / Wan Siti Adibah Wan Dahalan - Wan Siti Adibah, Wan Dahalan (2011)

(untitled)
This thesis seeks to examine the shipment of chemical substances otherwise known as hazardous and noxious substances (HNS) through the Straits of Malacca (SOM). The SOM is important to Malaysia from navigational, economic, environmental and strategic considerations. In this thesis, the term “chemical shipments” are also referred to as Hazardous and Noxious Substances (HNS) shipments and both terms are used with the same meaning. The legal framework of the study comprises international laws and international environmental law principles, regional laws such as the Asia-Pacific MOU on Port State Control of 1993 and 2009, and domestic laws of Malaysia, Indonesia and Singapore. Collectively, Malaysia, Indonesia and Singapore are referred to as the straits States. With the ratification of the 1982 LOSC by the strait States, the Straits of Malacca and Singapore fall within the legal definition of “a strait used for international navigation” and are governed by the transit passage regime encapsulated in Part III of the 1982 LOSC. This thesis examines HNS shipments through the SOM as follows: The thesis has six chapters. Chapter One deals with the Overview. Chapters Two analyses the current regime of navigation and shipping statistics as recorded at vessel traffic systems at several ports in Peninsular Malaysia bordering the SOM namely Klang, Penang and Johore, shipping incidents in the designated sea lanes of the SOM with a special focus on the increasing number of ships reporting and types of ships carrying HNS at the Klang Vessel Traffic System and chemical pollution and marine scientific research on chemical pollution control. It argues in conclusion that the status quo on legal aspects in the SOM must change. Chapter Three analyses international environmental law principles, HNS shipments on safety and security of navigation, marine pollution control, liability and compensation framework and waste control regulations for HNS pollution. The 1996 HNS Convention and the 2010 iii Protocol HNS Convention are not enforced yet and have not been ratified by the strait States. It concludes by stressing the importance of ratification of the HNS Conventions. Chapter Four analyses the sub-regional response action plans for chemical spill containment or HNS substances with a focus on comparative analysis with the oil spill response action plans. It stresses the need to adopt a sub-regional approach to chemical or HNS pollution as there is none available at present. Chapter Five assesses the adequacy of Malaysian, Indonesian and Singaporean laws for chemical or HNS shipments and in particular on liability and compensation. It underscores the importance of adopting the chemical or HNS liability and compensation provisions of chemical or HNS Conventions as the claimant of chemical or HNS incident will face problems in the absence of the element of strict liability and ship and cargo owners will face problems in the absence of compulsory insurance against liabilities arising from chemical or HNS incidents. Chapter Six contains several Recommendations and stresses to develop a SOM sub-regional model on chemical or HNS pollution response and a national Malaysian approach to the regulation of chemical or HNS shipments through the SOM and presents the Conclusion to the thesis. The law is stated as at January 2010 and includes updates as recent as September 2010.